A Functional Comparison of Treatment of Intrinsic Sphincter Deficiency with Muscle‐Derived and Adipose Tissue‐Derived Stem Cells. Issue 10 (13th September 2018) - Cui, Lingang; Meng, Qingjun; Wen, Jianguo; Gao, Zhan; Yan, Zechen; Tian, Yudong; Xu, Pengchao; He, Xianfei; Yu, Haizhou; Lian, Pengchao
Summary: This study investigated the effect of muscle‐derived stem cells (MDSCs) and adipose tissue‐derived stem cells (ADSCs) in the treatment of stress urinary incontinence (SUI) and their differences in a rat model. MDSCs and ADSC were isolated from rats ( n = 10), examined for their properties, and labeled with enhanced green fluorescent protein (EGFP) and β‐galactosidase (β‐gal) gene. Rats received bladder‐neck and transurethral sphincter injection of EGFP‐labeled MDSCs and β‐gal gene‐labeled ADSC and injection of D‐Hanks as a control ( n = 24 each group). At 0, 15, 30, and 60 days after cells injection, urinary voiding function was assessed by urine dynamics detector. The rats were killed to harvest their urethras for tracking of MDSCs and ADSC. Western blotting and quantitative real‐time reverse transcription PCR (qRT‐PCR) was performed to detect smooth muscle contents. Urodynamic test showed that MDSCs and ADSC improved the function of urination in rats with intrinsic sphincter deficiency (ISD), and effect of MDSCs‐treatment was more pronounced. In addition, histologic analysis showed that the MDSCs and ADSC‐treated groups had significantly higher myosin and α‐smooth muscle actin (α‐SMA) content than the control group. Compared with ADSC‐treated groups, the MDSCs‐treated groups in myosin and α‐SMA content showed the tendency of increase. In summary, MDSCs and ADSCs have obvious effects in the treatment and/or prevention of ISD and transplantation of MDSCs is more effective than ADSC. © 2018 IUBMB Life, 70(10):976–984, 2018